2023
DOI: 10.3389/fphar.2023.1185380
|View full text |Cite
|
Sign up to set email alerts
|

Function and prognostic value of basement membrane -related genes in lung adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) has become a common cause of cancer-related death. Many studies have shown that the basement membrane (BM) is associated with the development of cancer. However, BM-related gene expression and its relationship to LUAD prognosis remains unclear.Methods: BM-related genes from previous studies were used. Clinical and mRNA expression information were obtained from TCGA database. Cox, minimum absolute contraction, and selection operator regression were applied to analyze the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…BM invasion is pivotal for tumor metastasis (Chang and Chaudhuri 2019), spotlighting the significance of BM-related genes (BMGs) in cancer research. Studies have shown that models based on BMGs effectively predict outcomes and immunotherapy impacts in solid tumors like lung adenocarcinoma (Zhang et al 2023), pancreatic cancer (Zhou et al 2024), and prostate cancer (Xie et al 2024). In 2023, Sun W et al (Sun et al 2023) developed a prognostic model for HCC using BMGs, aiding clinicians in prognosis assessment and guiding immunotherapy and medication choices.…”
Section: Introductionmentioning
confidence: 99%
“…BM invasion is pivotal for tumor metastasis (Chang and Chaudhuri 2019), spotlighting the significance of BM-related genes (BMGs) in cancer research. Studies have shown that models based on BMGs effectively predict outcomes and immunotherapy impacts in solid tumors like lung adenocarcinoma (Zhang et al 2023), pancreatic cancer (Zhou et al 2024), and prostate cancer (Xie et al 2024). In 2023, Sun W et al (Sun et al 2023) developed a prognostic model for HCC using BMGs, aiding clinicians in prognosis assessment and guiding immunotherapy and medication choices.…”
Section: Introductionmentioning
confidence: 99%